أثر استخدام إستراتيجية التعلم التعاوني لتطوير مهارة القراءة لدي طلاب المرحلة الثانوية بالسودان ( دراسة حالة محلية الدويم ) (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
The study aimed to identify the effect of using cooperative learning strategy on students learning of reading skill, where the sample of the study consisted of (200) students from the Sudanese secondary schools in Al-Duiem locality who were divided into experimental group and control group. The researcher used pre and post test to collect the data, where the result of the study showed that using cooperative learning stimulate students to learn and help them achieve their goals., The results of the study showed that the cooperative learning develops the social skills of the students. هدفت الدراسة للتعرف على اثر استخدام إستراتيجية التعلم التعاوني لتعليم الطلاب مهارة القراءة . تكونت عينة الدراسة من 200 طالب من المرحلة الثاوية السودانية من محلية الدويم تم تقسيمهم إلى مجموعة تجريبية ومجموعة ضابطة . استخدم الباحث الاختبار القبلي و البعدي لجمع المعلومات حيث أظهرت نتائج الدراسة أن هنالك أثر لاستخدام التعلم التعاوني على قدرة الطلاب على القراءة كما أظهرت نتائج الدراسة استخدام التعلم التعاوني يحفز الطلاب على التعلم و يساعدهم في تحقيق أهدافهم كما أظهرت نتائج الدراسة أن التعلم التعاوني يطور المهارات الاجتماعية لدى الطلاب.